Evaluation of candidate spermatogonial markers ID4 and GPR125 in testes of adult human cadaveric organ donors. (5th June 2014) - Sachs, C.; Robinson, B. D.; Andres Martin, L.; Webster, T.; Gilbert, M.; Lo, H.‐Y.; Rafii, S.; Ng, C. K.; Seandel, M.
Summary The optimal markers for human spermatogonial stem cells (SSCs) are not known. Among the genes recently linked to SSCs in mice and other animals are the basic helix‐loop‐helix transcription factor ID4 and the orphan G‐protein‐coupled receptor GPR125. While ID4 and GPR125 are considered putative markers for SSCs, they have not been evaluated for coexpression in human tissue. Furthermore, neither the size nor the character of the human spermatogonial populations that express ID4 and GPR125, respectively, are known. A major barrier to addressing these questions is the availability of healthy adult testis tissue from donors with no known reproductive health problems. To overcome this obstacle, we have employed healthy testicular tissue from a novel set of organ donors (n = 16; aged 17–68 years) who were undergoing post‐mortem clinical organ procurement. Using immunolabelling, we found that ID4 and GPR125 are expressed on partially overlapping spermatogonial populations and are more broadly expressed in the normal adult human testis. In addition, we found that expression of ID4 remained stable during ageing. These findings suggest that ID4 and GPR125 could be efficacious for identifying previously unrecognized human spermatogonial subpopulations in conjunction with other putative human stem cell markers, both in younger and older donors.